(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The national consciousness, national pride, and national pride of our people are growing, and their spiritual world is becoming richer day by day. This creates an opportunity to further strengthen the moral foundation of our independent state. Problems in our education and ways to solve those issues are cited in this article.